2012
DOI: 10.1038/ja.2011.137
|View full text |Cite
|
Sign up to set email alerts
|

Catechoserine, a new catecholate-type inhibitor of tumor cell invasion from Streptomyces sp.

Abstract: Microbial natural products represent the primary resource for drug discovery, accounting for 420 000 bioactive compounds discovered to date. 1 The majority of microbial drug discovery research has focused on actinomycetes, in particular strains of the chemically prolific genus Streptomyces. Drug discovery efforts from actinomycetes, however, have been in decline, in part because of the relatively high frequency of the isolation of known compounds. To overcome this problem, extensive attempts have been directed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…Subsequent 1D and 2D NMR spectroscopy analyses (Table S3, Figures S2–S6) confirmed that the active compound has an identical planar structure to that of linear enterobactin . Optical rotation measurement ([α] D 23 + 13, c 0.10, MeOH) confirmed that the absolute stereochemistry of LinEnt matched the published form, which is constructed from l -serine …”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…Subsequent 1D and 2D NMR spectroscopy analyses (Table S3, Figures S2–S6) confirmed that the active compound has an identical planar structure to that of linear enterobactin . Optical rotation measurement ([α] D 23 + 13, c 0.10, MeOH) confirmed that the absolute stereochemistry of LinEnt matched the published form, which is constructed from l -serine …”
Section: Resultsmentioning
confidence: 70%
“…Tandem mass spectrometry (MS/MS) analysis of this compound (Figure S1) revealed a fragmentation pattern that matches substructures of linear enterobactin (LinEnt, Figure c), a byproduct of enterobactin biosynthesis and utilization . Subsequent 1D and 2D NMR spectroscopy analyses (Table S3, Figures S2–S6) confirmed that the active compound has an identical planar structure to that of linear enterobactin . Optical rotation measurement ([α] D 23 + 13, c 0.10, MeOH) confirmed that the absolute stereochemistry of LinEnt matched the published form, which is constructed from l -serine …”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Mycelia were harvested after incubation of the flask on a reciprocal shaker (120 spm) at 28°C for 3 days. The seed (30) in a 500-ml baffled flask on a reciprocal shaker (120 spm) at 28°C, followed by incubation for 3 days. The culture broth was extracted twice with an equal volume of ethyl acetate.…”
Section: Methodsmentioning
confidence: 99%
“…TP-A0874, was isolated from a compost sample collected in Ishikawa, Japan, and found to produce a new catecholate derivative designated catechoserine, along with two known biosynthetically related metabolites, N , N ′-bis(2,3-dihydroxybenzoyl)- O - l -seryl- l -serine and N , N ′, N ′-tris(2,3-dihydroxybenzoyl)- O - l -seryl- O - l -seryl- l -serine. These three compounds share an N -2,3-dihydroxybenzoyl-L-serine as a common structural unit and inhibit the invasion of murine colon carcinoma 26-L5 cells ( 1 ). To identify the biosynthetic gene cluster for these compounds and assess the potential to produce other secondary metabolites, we sequenced the genome of Streptomyces sp.…”
Section: Genome Announcementmentioning
confidence: 99%